CHILDREN’S CEREMONIAL SONGS RELATED TO THE HIJRI-LUNAR CALENDAR: FOLKLORE, CALENDAR TIME, AND CHILDREN’S PERFORMANCE - Esanov Alijon Mengbayevich (International Journal of Literature and Language Studies, 2026)
Abstract. This article provides a scientific and theoretical analysis of children’s ceremonial songs related to the Hijri-lunar calendar, particularly the songs and chants that occupy a special place in Uzbek children’s folklore, such as “Yo Ramazon,” “Ramazon aytimlari” (Ramadan chants), and children’s chants connected with the eve of Eid and the Eid holidays. The study examines the role of the lunar calendar in determining religious and cultural time, the ceremonial function of children’s performance, the poetic structure of the songs, their social and communicative function, and their modern transformation. The Hijri calendar consists of twelve lunar months and is used to determine the dates of religious ceremonies. Since the lunar year is approximately eleven days shorter than the solar year, Ramadan and other dates shift every year in the Gregorian calendar. This feature demonstrates that children’s ceremonial songs are connected not to a natural season, but to sacralized religious time.